PTP1B Inhibitory Activity of Flavonoids from the Roots of Astragalus membranaceus Bunge - Pham, Thi Ly; Ha, Manh Tuan; Min, Byung Sun; Kim, Jeong Ah (Natural product sciences, 2025)
The roots of Astragalus membranaceus Bunge have long been used in herbal medicine for their diverse biological activities. Notably, its potential anti-diabetic properties have been extensively studied, highlighting promising therapeutic prospects. In this study, we conducted a comprehensive investigation focusing on flavonoid components from the roots of A. membranaceus and their PTP1B inhibitory activity. As a result, we isolated a total of 24 flavonoids, among which formonentin (1), pratensein (3), and vesticarpan (19) emerged as the most potent inhibitors against PTP1B with IC50 value of 10.9 ± 1.09 μM, 10.0 ± 1.71 μM, and 10.3 ± 1.31 μM, respectively. Additionally, through the enzyme kinetic analysis, the inhibition mode of compound 19 was determined as a competitive inhibitor, with Ki value of 7.6 ± 1.17 μM. Furthermore, the molecular docking simulation elucidated the binding mechanism of compound 19 with PTP1B, mainly through van der Waals forces and hydrogen bonds. This study highlights the PTP1B inhibitory potential of the flavonoid constituents derived from the roots of A. membranaceus. Moreover, discovering vesticarpan (19) as a novel PTP1B inhibitor provides a significant foundation for further investigations to develop innovative therapeutic strategies for diabetes treatment. KCI Citation Count: 0